Willingness to Be Vaccinated Against COVID-19 Among People With HIV in the United States: Results From a National Survey - Wickersham, Jeffrey A.; Meyer, Jaimie P.; Shenoi, Sheela; Altice, Frederick L.; Barakat, Lydia Aoun; Virata, Michael; Olivares, Miriam; Maviglia, Francesca; Khati, Antoine; Shrestha, Roman (Frontiers in Medicine, 2022)
Background: Approximately 215 million Americans have been fully vaccinated for COVID-19, representing over 65% of the total population. People with HIV (PWH) may be more susceptible to COVID-19 infection or severe disease, elevating the importance of COVID-19 vaccination uptake in the population. We report results from a national survey of PWH to evaluate the likelihood of receiving a COVID-19 vaccine. Methods: We conducted an online survey of 1,030 PWH living in the United States between December 6, 2020 and January 8, 2021 to evaluate likelihood of receiving a COVID-19 vaccine. Results: Overall, participants were highly willing to be vaccinated, with 83.8% stating they “strongly agree” (65.7%) or “somewhat agree” (18.1%). Participants’ top vaccine-related concerns were side-effects (39.3%), safety (14.7%), and fair/equitable distribution of the vaccine to affected communities (13.6%). Participants were more willing to be vaccinated if they reported receiving an annual influenza vaccination (p<0.001), had previously tested positive for (p=0.043) COVID-19, had been hospitalized for (p=0.027) COVID-19 infection, or had an undetectable HIV viral load (p=0.002). Black (p<0.001), politically conservative (p<0.001), and participants with an annual income of ≤$19,999 (p=0.005) were significantly less willing to be vaccinated for COVID-19. Conclusions: The vast majority of PWH were willing to be vaccinated, though predominantly those who were already engaged in HIV care or directly affected by COVID-19. Findings from this large survey of PWH suggest intensive outreach efforts are needed to support engagement in vaccination programs, particularly among Black and politically conservative PWH.